Performance of primary Care Health professional in dengue prevention: difficulties in combating the vector (Research, Society and Development, 2022)
The article reports the performance of health workers, in communication with the population about the dissemination of information on dengue prevention. Objective: to analyze the scientific literature on the role of primary care health professionals in the prevention of dengue. Method: this study is an integrative review, carried out in November 2021, based on the identification and analysis of literature, based on the PUBMED, SciELO and LILACS databases, with the following descriptors: prevention, dengue and primary care. Results: The research was carried out by analyzing articles, and 10 articles were found available for use. Of these, eight (80%) were found on the LILACS platform and two (20%) on SciELO, with interpretation of positive and negative impacts or with both perspectives on the points addressed. Therefore, these studies address the role of health team professionals and emphasize the role of Community Health Agents (ACS) and Endemic Disease Control Agents (ACE) in the fight against dengue in basic units. In addition, they critically address the measures to minimize the problem in public health, listing the unpreparedness and lack of training of professionals.